Peningkatan Hasil Belajar Peserta Didik pada Keterampilan Menulis Puisi Menggunakan Model Problem Based Learning (PBL) di Kelas IV SD Negeri 04 Mungka - Asti, Asti; Desyandri, Desyandri (COGNITIVISM: Journal of Educational Research and Development, 2025)
This research aims to describe the improvement in student learning outcomes in poetry writing using the Problem Based Learning (PBL) model in grade IV SDN 04 Mungka. The type of research is Classroom Action Research (CAR) with a research procedure consisting of planning, implementation, observation, and reflection. Data collection techniques include tests and non-tests, with a total of 16 subjects in this study. The research results indicate that the teaching module in cycle I obtained an average of 83.3% (B), which increased in cycle II to 95.8% (SB). The implementation of teaching in the teacher aspect in cycle I obtained an average of 83.92% (B), which increased in cycle II to 96.42% (SB). The results of the implementation of student learning aspects in cycle I showed an average of 83.92% (B), which increased in cycle II to 96.42% (SB). The learning outcomes of students in cycle I meeting I from the assessment of attitude aspects indicated that 3 students displayed positive attitudes and 3 students displayed negative attitudes. This improved in cycle I meeting II with 4 students showing positive attitudes and 1 student showing a negative attitude in cycle II. The learning outcomes of students, when viewed from knowledge and skills aspects, had an average of 78.7% in cycle I, which increased to 90% in cycle II. It can be concluded that the PBL model can enhance student learning outcomes in poetry writing lessons in grade IV at SDN 04 Mungka